UPAYA PENINGKATAN LITERASI DI DESA LAMPEJI MELALUI MEDIA RUANG BACA - Achmad Saifur R; Arini Salsabila; Zida Rizqi A; Ihya Nurina R; Muhammad Fadlin T; Muhammad Khoiruddin; Galuh Adi Fransiska (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Reading activities are activities that need to be preserved and developed in Indonesia. According to research entitled